PENGARUH RETURN ON ASSET, RETURN ON EQUITY, DAN NET PROFIT MARGIN TERHADAP PRICE EARNING RATIO (Studi Empiris pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun2010-2012) - Christina Dewi, 10.05.52.0030; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2014)
Price Earning Ratio (PER) is a part of the rasio market that determines how the market give value or price in a company. The ability gainful an entreprise in make one of the main Â considerations most investors to invest. This research is aimed to test about Â the Influence of Return on Assets, Return on Equity, and Net Profit Margin againts price earning ratio on companies listed in Indonesia Stock Exchange (IDX) 2010-2012. Collection data uses the method purposive sampling againtst severalmanufacturing companies listed on the Â Indonesia Stock Exchange (IDX) in 2010 â 2012. There are 228 companies that using as a sample. Analysis data that the use is Â linear regression of multiple test assumption classical consist of test Â normality, multicollinearity, autocorrelation test, test heterokedastisitas, coefficient determination , F test, and statistic test T. The results showed that the Â Return on Assets influences positif and itâs not significant for Price Earning Ratio, Return on Equity influences significant positive to Price Earning Ratio, and Net Profit Margin influences significant positive toÂ Price Earning Ratio. Keywords: Return On Asset, Return On Equity, Net Profit Margin, Price Earning Ratio